Extraction, purification and characterisation of a milk-clotting protease from 'kesinai' (Streblus asper Lour.) leaves - Pagthinathan, Mylvaganam; Mohd Ghazali, Hasanah; Abd Manap, Mohd Yazid; Foo, Hooi Ling (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Extracts from ‘kesinai’ (Streblus asper) leaves were investigated as a potential source of enzymes that can serve as an alternative to calf rennet in cheese making. Different types of extraction buffers were investigated namely sodium acetate buffer (pH 4.2-5.0), phosphate buffer (pH 6.0-7.0) and Tris-HCl buffer (pH 7.0-9.0). Finally, the milk-clotting enzyme was extracted using 100 mM Tris-HCl buffer (pH 7.4) with and without 5.0 mg/mL polyvinylpyrrolidone, 0.015 mL/mL Triton X-100 and 2 mM sodium metabisulphite. Purification was carried out using acetone precipitation, and ion-exchange and size-exclusion chromatographic techniques. Results showed that 100 mM Tris-HCl buffer (pH 7.4) was the most efficient extraction buffer among the buffers used in the extraction study. After the final purification step of size-exclusion chromatography, the enzyme was purified 3.3-fold with 42.3% of recovery. The enzyme showed an optimum temperature and pH at 60°C and pH 7.4, respectively. The enzyme was stable up to 70°C for one hour and the partially purified enzyme retained 83% and 96% of its original activity at pH 6.0 and 8.0, respectively. The molecular weight of the partially enzyme was estimated to be 75.8 kDa on SDS-PAGE. The milk-clotting activity of ‘kesinai’ enzyme was found to be lower than that of commercial Mucor rennet.